Hukum Tambahan Pajak Restoran dalam Jual Beli Perspektif Kompilasi Hukum Ekonomi Syariah dan Peraturan Daerah (PERDA) Kota Medan No 5 Tahun 2011: (Studi Kasus Restoran Mie Gacoan di Jl SM Raja Kota Medan) - Iqklimah, Iqklimah; Ahmad Zuhri (Universitas Ekasakti, 2024)
Buying and selling is a profitable commercial activity that involves both buyers and sellers. However, not all purchasing and selling operations contain Islamic law-compliant lessons, one example is restaurant transactions. In actuality, many restaurants charge an extra tax on their transactions, including the Mie Gacoan restaurant on Jl SM Raja, Medan City. There are differences in rules governing additional restaurant tax laws in purchasing and selling, particularly from the perspective of the Compilation of Sharia Economic Law, which holds that it is invalid due to buyer compulsion. Meanwhile, according to Medan City Regional Regulation Number 5 of 2011, the extra tax on purchasing and selling is legitimate because it is a government-mandated requirement. The aim of this research is to find out which opinion is most relevant to the benefit of today's people from both of these laws. The research method used is interviews with open-ended questions mixed with library research methods to investigate the needed documents utilizing empirical juridical research, comparative approaches, and legal sociology.